The Lawyer as Conflict Manager: Exploring the Lawyer’s Role in ADR, Especially as an Advisor in Mediation and as Lawyer-Mediator in Germany - Fritz, Roland; Lefèvre, Julia (Studia Prawa Publicznego, 2025)
This article advocates redefining the lawyer’s role as a conflict manager, shifting from adversarial approaches to interest-based, consensual conflict resolution. Although litigation remains the norm, alternative dispute resolution (ADR), especially mediation, offers significant benefits that are often underutilized. Lawyers can act as advisors, guiding clients to select and engage in ADR processes tailored to their needs, or as mediators, facilitating neutral, self-determined outcomes. The article examines key ADR methods, including mediation, collaborative practice, and procedural hybrids like med-arb, highlighting their applications, advantages and challenges. Special emphasis is placed on the lawyer’s dual role: advising clients during ADR proceedings and serving as a neutral third party in mediation. Preparation, confidentiality and risk analysis are central to the lawyer’s responsibilities in ensuring effective mediation outcomes. Additionally, the article addresses the professional and ethical considerations for lawyers acting as mediators, including adherence to legal standards and avoidance of conflicts of interest. It argues that adopting a conflict-management approach not only aligns with legal professional standards but also enhances client satisfaction and outcomes by prioritizing efficient, amicable solutions over confrontational disputes. By integrating conflict management into legal practice, lawyers can expand their professional scope, offering valuable alternatives that promote long-term cooperation and resolution beyond the courtroom.